METHODS, MEANS, AND TECHNOLOGIES FOR THE DEVELOPMENT OF HEALTH-ORIENTED PEDAGOGICAL THINKING IN UNIVERSITY STUDENTS - Umarova Dilfuza Mamatkulovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the multifaceted process of developing health-oriented pedagogical thinking among students in higher education institutions. As the demands of modern life increasingly affect the physical and mental well-being of young people, universities are tasked with not only delivering academic content but also cultivating students’ awareness, responsibility, and behavior related to personal and social health. The article emphasizes the strategic integration of interactive teaching methods, innovative tools, and digital technologies to foster a culture of health and well-being on campus. It discusses the educator’s pivotal role as both a facilitator and role model, the importance of interdisciplinary approaches, and the inclusion of health-related content across all areas of study.